Constitutional responsibility of political parties as pillars of democracy in the perspective of Indonesian constitutional law - Putu Wahyu Widiartana; Bagus Gede Ari Rama; Ni Putu Ega Maha Wiryanthi (Cessie : Jurnal Ilmiah Hukum, 2025)
Democracy is a fundamental principle within the Indonesian state system as reflected in the 1945 Constitution (UUD 1945), where political parties play a key role as a pillar in bridging the people and the government. The constitutional responsibility of political parties within the Indonesian constitutional system encompasses not only compliance with the law but also moral and ethical aspects in realizing a clean, transparent, and accountable government. This study aims to examine the regulation of the constitutional responsibility of political parties from the perspective of Indonesian constitutional law, as well as the relationship between this responsibility and the quality of democracy that is fostered. The research method used is normative legal research with legislative, conceptual, and documentary study approaches. The analysis is conducted qualitatively to explore the understanding of the implementation of the constitutional responsibility of political parties and its impact on the quality of democracy. The findings indicate that, although clear legal provisions exist regarding the role of political parties, their implementation still faces significant challenges, such as the practice of money politics and the pragmatic tendencies of parties. Therefore, stricter supervision is necessary to ensure that political parties fulfill their constitutional responsibilities effectively, thereby improving the quality of democracy in Indonesia. This study is expected to contribute to the development of constitutional law theory and practice, as well as strengthen the role of political parties in reinforcing Indonesia's democratic system.